Productivity of Maize–Cowpea Intercrops as Influenced by Cowpea Varieties and Row Arrangements in the Sudan Savannah of Kano, Nigeria - Bello, Tasiu Tukur; Habib, Fatima Muhammad; Shittu, Emmanuel Abraham (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
This field study was conducted during the 2023 rainy season at two sites in Kano State, Nigeria, to evaluate maize–cowpea intercropping performance as influenced by different row arrangements (RA) and cowpea varieties. A split-plot design with three replications was used, assessing four intercropping arrangements (1:1, 1:2, 2:1, and 2:2) and two cowpea varieties (SAMPEA 19 and SAMPEA 21), alongside sole crops. Results indicated that SAMPEA 21 significantly (p < 0.001) enhanced maize vegetative growth, particularly in the 1M:1C arrangement, which produced the tallest plants and highest maize grain yield (2.3 t ha⁻¹) at BUK. In contrast, at Minjibir, the 1:2 arrangement significantly (p < 0.05) reduced maize yield (0.95 t ha⁻¹). Although yield components other than grain yield were not significantly affected (p > 0.05) by variety or row arrangement, intercropping systems generally improved land use efficiency. The 1M:1C arrangement with SAMPEA 21 consistently recorded the highest land equivalent ratio (LER), reaching 1.64 at BUK and 1.58 at Minjibir. The study concludes that a 1M:1C intercropping system using SAMPEA 21 optimizes productivity and resource use in the Sudano-Sahelian agroecological zone and is therefore recommended for adoption by farmers in the region.